Knowledge deficit and fear of COVID-19 among higher education students during the first wave of the pandemic and implications for public health: a multi-country cross-sectional survey - Neamin M. Berhe; Sarah Van de Velde; Fatemeh Rabiee-Khan; Claudia van der Heijde; Peter Vonk; Veerle Buffel; Edwin Wouters; Guido Van Hal (BMC, 2022)
Abstract Background Public health measures such as physical distancing and distance learning have been implemented during the COVID-19 pandemic. COVID-19 related knowledge deficit can increase fear that leads to negative mental health and COVID-19, especially among adolescents. Therefore, our study aimed to assess COVID-19 related knowledge deficit and its association with fear among higher education (HE) students during the first wave of COVID-19. Methods A cross-sectional survey, COVID-19 International Students Well-being Study (C-19 ISWS) was conducted in 133 Higher Education Institutions (HEIs) in 26 countries between April 27 and July 7, 2020. A stratified convenience sampling technique was used. Descriptive, bivariate, mixed-effect logistic regression analyses were conducted using R software. Results Out of 127,362 respondents, 72.1% were female, and 76.5% did not report a previous history of confirmed COVID-19. The majority of those without the previous infection 81,645 (83.7%) were from 21 European countries while the rest 15,850 (16.3%) were from 5 non-European countries. The most frequent correct response to COVID-19 related knowledge questions among respondents was having the virus without having symptoms (94.3%). Compared to participants with good knowledge, the odds of being afraid of acquiring SARS-COV-2 infection among those with poor knowledge was 1.05 (95%CI:1.03,1.08) and the odds of being afraid of contracting severe COVID-19 was 1.36 (95%CI:1.31,1.40). Conclusion COVID-19 related knowledge was independently associated with both fear of acquiring SARS-COV-2 infection as well as contracting severe COVID-19. Our findings will serve as a basis for public health response for both the current and similar future pandemics by highlighting the need for addressing the COVID-19 knowledge deficit to fight the infodemic and prevent negative mental health outcomes.